Physical activity level and fall risk among community-dwelling older adults - Low, Sok Teng; Balaraman, Thirumalaya (The Society of Physical Therapy Science, 2017)
[Purpose] To find the physical activity level and fall risk among the community-dwelling Malaysian older adults and determine the correlation between them. [Subjects and Methods] A cross-sectional study was conducted in which, the physical activity level was evaluated using the Rapid Assessment of Physical Activity questionnaire and fall risk with Fall Risk Assessment Tool. Subjects recruited were 132 community-dwelling Malaysian older adults using the convenience sampling method. [Results] The majority of the participants were under the category of under-active regular light-activities and most of them reported low fall risk. The statistical analysis using Fisher’s exact test did not show a significant correlation between physical activity level and fall risk. [Conclusion] The majority of community-dwelling Malaysian older adults are performing some form of physical activity and in low fall risk category. But this study did not find any significant correlation between physical activity level and fall risk among community-dwelling older adults in Malaysia.